Violência : uma análise do bullying juvenil e da violência doméstica contra mulher - Rizzotto, Júlia Sbroglio (2020)
This dissertation presents two articles about Economics of Crime. The first seeks to analyze the impact of different dimensions of bullying: physical, psychological and indirect in the school performance of Brazilian students. For this analysis, data from the International Student Assessment Program (PISA) for the year 2015 was used. The methodology used was the Propensity Score Matching (PSM) and Quantile Treatment Effects (QTE). Results showed that physical bullying (picking up and have belongings destroyed) is detrimental to the performance of school students. The destruction of students' belongings negatively impacted only the reading grade, not being statistically significant for other grades. Psychological bullying (have rumors spread, making jokes and being threatened), paradoxically, did not negatively affect the grades of students. Being excluded by the class, considered as indirect bullying, also did not have significance in the disciplines studied. Bullying has several consequences for the student besides the reduction of school performance that can lead to school dropout and sometimes difficulties in the labor market. Therefore, studying this phenomenon by means of the school behavior is a matter of importance to society. The second paper aims to analyze if there is a wage difference between women who were victims of domestic violence by known person and those who were not. Domestic violence against women damages the life of the victim. The aggressions affect her insertion in the labor market, which is reflected in loss of productivity, in search of better jobs and, consequently, her financial independence. In order to do so, data from the National Health Survey (PNS) for the year 2013 were used. The methodological approach consists of performing a wage decomposition of Oaxaca-Blinder and a decomposition by quantile (RIF-regression) in order to obtain estimates for income amounts. The results showed that women who suffered domestic violence from a known person receive about 19% less than those who did not. In addition, the analysis by quantile pointed out that this difference is greater in the upper and lower tails. It´s concluded that violence impacts women's salaries and it´s necessary to implement stricter public policies so that the incidence of this aggression reduces and provide victims with greater security.